Alkali -silica reaction and its dynamic relationship with cement pore solution in highly reactive systems. (2nd January 2023) - Balachandran, Chandni; Muñoz, Jose F.; Peethamparan, Sulapha; Arnold, Terence S.
Highlights: A multi-analytical approach was applied to study ASR mechanism in a highly reactive mortar system containing fused silica. ASR products in this system comprised of a low calcium product (ASR-type gel) and a high calcium product (CSH-type gel). A dynamic relationship between evolution of the pore solution chemistry and the nature of ASR products was established. Insights into how pore solution composition affects ASR products is key to designing a robust accelerated ASR test method. Abstract: Despite extensive research, the relationship between the progression of alkali-silica reaction (ASR) and the cement hydration mechanism, particularly the influence of the pore solution composition on the nature of reaction products is not thoroughly understood. A multi-analytical approach was applied to study ASR mechanism under accelerated conditions using a mortar system comprising of fused silica aggregates. For the first time, large field SEM mapping was used to correlate physical expansion with the composition, distribution and amount of ASR reaction products produced over time. A three-stage behavioral model was proposed to explain the dynamic relationship between ASR progression and pore solution composition. The results confirmed the co-existence of two phases within the ASR products: a CSH- type gel and an ASR-type gel. The relative abundance of one gel type over the other was dictated by their accessibility to the pore solution, which in turn influences how ASR propagates through the microstructure.